Contrast-enhanced ultrasound improves accurate identification of appendiceal mucinous adenocarcinoma in an old patient: A case report. Issue 35 (August 2016) - Shang, Jing; Ruan, Li-tao; Dang, Ying; Wang, Yun-yue; Song, Yan; Lian, Jie
Abstract: Background: Adenocarcinoma of appendiceal origin is far rarer than other colorectal carcinomas and its preoperative diagnosis is challenging. To our knowledge, utility of contrast-enhanced ultrasound (CEUS) to diagnose it is much less. Method: A 61-year-old man presented with abdominal pain in the right lower quadrant for 20 days. In order to fulfill an accurately preoperative diagnosis, he received laboratory and imaging tests such as carcinoembryonic antigen (CEA), computer tomography (CT), CEUS and endoscope. Diagnosis and Intervention: He was initially suspected of suffering appendicitis, while his white blood cell count was normal and carcinoembryonic antigen (CEA) in serum was remarkably increased. Both routine ultrasound and computer tomography (CT) examinations supported suppurative appendicitis. The overall data, however, failed to excluded neoplastic pathology thoroughly. Therefore, CEUS was carried out and showed an inhomogeneous enhancement intra the lesion located in the body of the appendix, which made our consideration of neoplasm. The result of the follow-up biopsy guided by endoscope was consistent with appendiceal tumor. The patient received laparoscopic right hemicolectomy. Histopathology confirmed as well differentiated mucinous adenocarcinoma of appendix origin. His postoperative course was uneventful, and he had a regular diet again without any complaint. Result: Serum CEA was remarkably increased (12.00 ng/mL). Both routine ultrasound and CT examinations supported suppurative appendicitis. However, CEUS examination showed an inhomogeneous enhancement intra the lesion located in the body of the appendix, which made our consideration of neoplasm. The follow-up biopsy guided by endoscope and surgical specimens confirmed as well differentiated mucinous adenocarcinoma of appendix origin. Conclusion: Most mucinous adenocarcinoma mimicking appendicitis results in difficult diagnosis preoperatively. Clinician and radiologist should be aware of it when old patient presented with appendicitis especially along with high level of CEA.